An absolute radiocarbon chronology for the world heritage site of Sarvestan (SW Iran): A late Sasanian heritage in early Islamic era. (12th October 2021) - Djamali, Morteza; Capano, Manuela; Askari‐Chaverdi, Alireza; Faucherre, Nicolas; Guibal, Frédéric; Northedge, Alastair; Rashidian, Elnaz; Tuna, Thibaut; Bard, Edouard
Abstract: This study presents a new precise radiocarbon chronology for the World Heritage site of Sarvestan (SW Iran). The monument is a key construction in the history of architecture because it is a typical Sasanian construction built during the late Sasanian or early Islamic period. Previous attempts to date the monument have suggested the ages ranging from the middle Sasanian (fifth century CE) to early Abbasid (ninth century CE) era. These age estimations are based on the analysis of architectural plans and techniques, and a few radiocarbon dates with very large age uncertainties. This paper presents the results of a systematic radiocarbon dating of timbers in the walls and charcoals in plaster mortars used in the main dome of the monument. It further applies wiggle matching technique and R_Combine function to substantially reduce the age uncertainties in wood sections. The results indicate that a major construction work was undertaken sometime between 658 and 683 CE, the century of the invasion of Fars by Muslim Arabs. This finding pushes back the age of Sarvestan for two centuries and suggests that the monument was built at the transitional period between Sasanian to Islamic era. Sarvestan would have been an architectural project designed and possibly initiated during the late Sasanian period but mainly accomplished during the second half of the seventh century CE. It can thus be considered a late Sasanian heritage in early Islamic period. Its construction at a time of political unrest further suggests that some areas of Fars may have benefited from certain socio‐political stabilities during the expansion of Islam into the east at mid‐ to late seventh century CE.